2023
DOI: 10.1002/admt.202202124
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐Responsive Microneedle Patch With Variable Crosslinking Density and Flexible Core–Shell Structure for Insulin Delivery

Abstract: Developing glucose-responsive microneedle patches with features of simple preparation, high insulin loading, and safety has a great contribution to the treatment of diabetic patients. In this work, a novel glucose-responsive core-shell microneedle patch is prepared from biocompatible materials by a facile process. The exterior glucose-responsive shell is composed of polyvinyl alcohol (PVA) and ɛ-polylysine modified with phenylboronic acid , and the inner flexible core is prepared by pure PVA loaded with insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The pKa of PBA is 8.8-8.9 [38], which makes it prone to aggregation in the body, thereby limiting its ability to bind to glucose molecules to some extent [39]. To reduce the usage of glucose-responsive materials, microneedle patches with variable crosslinking densities in a core-shell structure [40], composite semi-interpenetrating hydrogel microneedles [41], and double-layered porous microneedle patches [42] have emerged. Additionally, modification of the structure of PBA can be employed to enhance its glucose sensitivity [43].…”
Section: Glucose-sensitive Microneedles Based On Pbamentioning
confidence: 99%
“…The pKa of PBA is 8.8-8.9 [38], which makes it prone to aggregation in the body, thereby limiting its ability to bind to glucose molecules to some extent [39]. To reduce the usage of glucose-responsive materials, microneedle patches with variable crosslinking densities in a core-shell structure [40], composite semi-interpenetrating hydrogel microneedles [41], and double-layered porous microneedle patches [42] have emerged. Additionally, modification of the structure of PBA can be employed to enhance its glucose sensitivity [43].…”
Section: Glucose-sensitive Microneedles Based On Pbamentioning
confidence: 99%
“…It has been reported that hydrogen peroxide (H 2 O 2 ) produced by GOx during glucose oxidation can bind to phenylboronic acid esters, leading to further degradation of the phenylboronic acid ester structure, which increases the sensitivity of the glucose response and promotes rapid insulin release. 26–28 Therefore, phenyl borate and its derivatives (PBE) in combination with GOx have been extensively utilized for diabetes treatment. 29–31…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is essential to develop a MNs system that can effectively regulate BGLs for the maximum possible duration. Currently, two approaches have been adopted to achieve this goal, including responsive release and increasing drug loading while expanding drug release time [25][26] . A few studies have developed responsive release MNs patches, aiming to achieve a sustained and controlled drug release profile [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%